A fibrose e a remodelação na rinossinusite crônica - Gregorio, Luciano Lobato [UNIFESP] (2018)
Introduction: Tissue remodeling is considered a key aspect in distinguishing between chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP) and without nasal polyps (CRSsNP), due to its purported central role in polyp formation. Objective: To evaluate the role of fibrosis and remodeling of the nasal mucosa, whether through biomechanical or molecular mechanisms, in CRS. Methods: Three studies were carried out. The first evaluated biomechanical mechanisms in the nasal mucosa. The behavior of interstitial hydrostatic pressure (IHP) was analyzed by recording a continuous infusion of saline solution into the nasal mucosa of patients with CRS, in nasal synechiae, and in control mucosa of individuals without sinonasal disease. Twenty participants (N=20) were examined, at different sites in the nasal cavity. Analysis of the infusion produced a plot of tissue pressure vs. volume infused, which would correspond to IHP, or, in a simplified manner, to mucosal compliance. For the second study, considering the essential role of TGF-β in mucosal remodeling, the existence of a subgroup of patients with CRSwNP who exhibit an exacerbated systemic inflammatory response, and in vitro studies demonstrating a potential relationship between pro- and anti-inflammatory factors, we decided to evaluate the direct influence of administration of a leukotriene receptor antagonist (montelukast) on the systemic production of TGF-β1 in CRS. Serum levels of TGF-β1 were measured in patients with CRSwNP (from different subgroups) and in controls, before and after administration of montelukast. Finally, the third study evaluated the possible variation of tissue levels of TGF-β1 in different regions of the nasal cavity and its relationship with serum levels in healthy controls and in individuals with sinonasal disease. Results: The experimental model of continuous saline injection in the nasal mucosa revealed mechanical dysfunction. IHP increased less in tissue from individuals with CRSwNP when compared to fibrotic tissue (nasal synechiae) and to control tissue. There was no significant difference between the latter two groups. In the control group, a statistically significant difference was found in the IHP reached in the middle and inferior turbinate sites. Regarding analysis of TGF-β1 levels before and after administration of an antileukotriene agent, no statistically significant differences were found, whether in the control group or in subgroups of patients with CRSwNP. Controls showed a trend toward lower serum levels of TGF-β1 in relation to the CRSwNP group. Comparison of tissue levels of TGF-β1 between different nasal sites did not reveal statistically significant differences. Samples taken from the middle meatus of patients with CRSwNP exhibited a numerically lower cytokine concentration in relation to the control and CRSsNP groups. A possible inverse pattern of TGF-β1 levels in the middle meatus/inferior turbinate of the CRSwNP group was found in comparison to the control and CRSsNP groups. Conclusion: These studies confirmed biomechanical involvement of the mucosa in patients with CRSwNP, with evidence of increased mucosal compliance, which might facilitate polyp formation. Montelukast administration had no appreciable impact on systemic TGF-β1 production in patients with CRSwNP, suggesting that use of this agent with a view to altering the remodeling process is a questionable practice. There was no significant difference in tissue levels of TGF-β1 at different sites of the nasal cavity in patients with CRS.